Clinical characteristics and natural history of asymptomatic erosive esophagitis - Jung, Sung Hoon; Oh, Jung Hwan; Kang, Sung-Goo (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: This study was designed to investigate risk factors related to asymptomatic erosive esophagitis and the natural history of both endoscopic findings and reflux-related symptoms in subjects with asymptomatic erosive esophagitis. Materials and Methods: On a retrospective basis, data were gathered from patients with erosive esophagitis (Los Angeles classification 3A) who had undergone endoscopic follow-up at St. Vincent Hospital. Data from 313 subjects with erosive esophagitis were investigated. Results: Most patients had mild esophagitis (grade A or B, Los Angeles classification); 198 (63.3%) had reflux symptoms, and 115 (36.7%) lacked typical or atypical symptoms. Asymptomatic erosive esophagitis was associated with non-smoking (odds ratio (OR), 2.4; 95% confidence interval (CI), 1.4-3.9) and lower body mass index (body mass index (BMI); OR, 1.5; 95% CI, 1.0-2.4), while 26% of subjects had recurring reflux-related symptoms. Younger subjects were more likely to have reflux-related symptoms (p<0.05). Conclusion: Non-smoking and lower BMI are associated with asymptomatic reflux esophagitis. Most asymptomatic subjects with erosive esophagitis remained stable and exhibited unchanged endoscopic findings.